Study on Preparation and Fresh-Keeping Performance of Plant Polyphenol-Nanocellulose Antibacterial Composite Films - Thompson, Kenneth; Brown, Patricia (Journal of Functional Materials and Applied Engineering, 2024)
In this work, a TEMPO/NaClO/NaClO₂ oxidation system based on 2,2,6,6-tetramethylpiperidin-1-oxyl was adopted to modify bacterial cellulose (BC) for the fabrication of TEMPO-oxidized cellulose nanofibrils (TOCNF). The as-prepared TOCNF was composited with rose polyphenol extract (RPE) to construct multifunctional rBC composite films with outstanding ultraviolet (UV) shielding and antibacterial fresh-keeping capacities. The influence of reaction temperature on TEMPO-mediated oxidation was systematically explored, and comprehensive characterization and analysis were carried out to evaluate the physicochemical properties of the rBC composite films. Experimental results demonstrate that moderately elevating reaction temperature can significantly boost oxidation efficiency. The TOCNF sample prepared at 60 °C (denoted BC-60) achieves a carboxyl content of 1.2 mmol/g. The incorporation of RPE does not destroy the well-ordered three-dimensional network architecture of TOCNF, while remarkably improving the mechanical strength and thermal stability of composite membranes. When the mass ratio of BC-60 to RPE reaches 1:10, the resultant rBC-T composite film delivers optimal overall performance, which can completely block full-spectrum UV light ranging from 200 nm to 400 nm and exert potent antibacterial activity against Escherichia coli. The diameter of inhibition zone reaches (13.02 ± 0.29) mm under a bacterial suspension mass fraction of 0.5%. After 10 days of cold storage at 4 °C, shrimp samples packaged with rBC-T exhibit a significantly lower pH value compared with those wrapped by pure BC-60 TOCNF films, which verifies the superior fresh-preserving capacity of the composite material. This rBC composite film possesses tremendous application potential in the field of functional food packaging.